The Role Of Islamic Education Teachers In Instilling Religious Moderation Values At Sma Teladan Helvetia Medan - Prihartini, Prihartini; Panggabean, Hadi Saputra (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2024)
The role of Islamic Education Teachers is crucial in instilling religious moderation values at SMA Teladan Helvetia Medan. The focus of this research is the role of Islamic Education Teachers in instilling religious moderation values to shape students' attitudes of tolerance. The problem in this study is the lack of implementation of tolerance among students, both in words and actions, at SMA Teladan Helvetia Medan. It is the responsibility of the Islamic Education teacher to cultivate tolerance attitudes through religious moderation values. The method used in this research is qualitative, with the researcher collecting information through observation, interviews, and documentation. The research results indicate that teachers have a good understanding of the concept of religious moderation and implement it through dialogical learning, extracurricular activities, and role modeling in daily interactions. Students' responses to these efforts are very positive, although challenges such as a lack of social environmental support and limited training for teachers remain. Proposed solutions include strengthening partnerships between schools, families, and communities, as well as enhancing teacher competencies. This study underscores the importance of the role of Islamic education teachers as agents of religious moderation to foster a tolerant and harmonious generation in a diverse society